DNA Viruses: The Really Big Ones (Giruses) - Van Etten, James L. (2010)
Viruses with genomes greater than 300 kb and up to 1200 kb are being discovered with increasing frequency. These large viruses (often called giruses) can encode up to 900 proteins and also many tRNAs. Consequently, these viruses have more protein-encoding genes than many bacteria, and the concept of small particle/small genome that once defined viruses is no longer valid. Giruses infect bacteria and animals although most of the recently discovered ones infect protists. Thus, genome gigantism is not restricted to a specific host or phylogenetic clade. To date, most of the giruses are associated with aqueous environments. Many of these large viruses (phycodnaviruses and Mimiviruses) probably have a common evolutionary ancestor with the poxviruses, iridoviruses, asfarviruses, ascoviruses, and a recently discovered Marseillevirus. One issue that is perhaps not appreciated by the microbiology community is that large viruses, even ones classified in the same family, can differ significantly in morphology, lifestyle, and genome structure. This review focuses on some of these differences rather than provides extensive details about individual viruses.